Low Tuberculosis Screening among Household Family Members of Tuberculosis Patients in Banyuarang and Sidowarek - Farid, Muhammad Rifqo Hafidzudin; Rananda, Arif; Aflahudin, Muhammad Ahda Naufal; Musalim, Dian Anggraini Permatasari; Hariftyani, Arisvia Sukma; Hanani, Nadya Kelfinta; Rofiq, Rodia Amanata; Aulia, Shazia Hafazhah; Sidqoh, Aida Badi’atus; Hewiz, Alya Shafira (Journal Medical Informatics Technology, 2023)
Early tuberculosis detection is vital, necessitating widespread screening. The WHO's End Tuberculosis strategy aims to combat this epidemic. Active screening is critical for identifying asymptomatic individuals at risk. Data from Pulorejo Primary Health Center, Jombang, indicates a low 10% coverage of suspected cases in 2021, particularly among household contacts, resulting in continued transmission, late detection, post-treatment symptoms, and even death. Therefore, this study was conducted to determine the number of screening participation of households of tuberculosis patients in Banyuarang and Sidowarek Village. This research is a descriptive observational. The data collected was primary data from questionnaires. The study population consisted of households of tuberculosis patients in the Banyuarang and Sidowarek Villages, Jombang Regency. Data collected from 12 respondents showed the prevalent characteristics among the 12 respondents were predominantly female, adult age, high school education, working, limited knowledge about tuberculosis, and easy access to healthcare services. Among the 12 respondents in Banyuarang and Sidowarek, 9 respondents had never been screened, while 3 respondents had undergone screening. The primary reasons for respondents not undergoing screening were lack of awareness regarding the necessity of screening and busy schedules.